Analysis of the baseline survey on the prevalence of Salmonella in holdings with breeding pigs in the EU, 2008 ‐ Part A: Salmonella prevalence estimates - European Food Safety Authority (EFSA Journal)
Abstract Salmonella is a major cause of food‐borne illness in humans. Farm animals and foods of animal origin are important sources of human Salmonella infections. This European Union‐wide Salmonella baseline survey was conducted in 2008 in holdings with breeding pigs. A total of 1,609 holdings housing and selling mainly breeding pigs (breeding holdings) and 3,508 holdings housing breeding pigs and selling mainly pigs for fattening or slaughter (production holdings) from 24 European Union Member States and two non‐Member States, were randomly selected and included in the survey. In each selected breeding and production holding, fresh voidedpooled faecal samples were collected from 10 randomly chosen pens, yards or groups of breeding pigs over six months of age, representing the different stages of the breeding herd. The pooled faecal samples from each holding were tested for Salmonella and the isolates were serotyped. The overall European Union prevalence of Salmonella‐positive holdings with breeding pigs was 31.8% and all but one of the 24 participating Member States detected Salmonella in at least one holding. The European Union prevalence of Salmonella‐positive breeding holdings was 28.7%, and prevalence varied from 0% to 64.0% among Member States. The European Union prevalence of Salmonella‐positive production holdings was 33.3%, while the Member States’ prevalence varied from 0% to 55.7%. The number of different Salmonella serovars isolated in breeding holdings and production holdings in the European Union was 54 and 88, respectively. Salmonella Derby and Salmonella Typhimurium predominated in both types of holdings. Breeding pigs may be an important source of dissemination of Salmonella throughout the pig‐production chain. The results of this survey provide valuable information for setting a Salmonella reduction target for breeding pigs and for assessing the impact of Salmonella transmission originating from holdings with breeding pigs